Application of Cooperative and Collaborative Learning Methods in Learning Strategic Decision Making Courses - Eni Susanti (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The purpose of this study is to determine the success rate of applying cooperative and collaborative learning methods in learning strategic decision-making courses for the International Relations Study Program. This research was conducted on students of the international relations study program class of 2020 Semester 5 who took strategic decision-making courses. The results of research from 3 classes obtained that students who obtained A grades of 67.65%, A- grades of 19.12%, B+ grades of 4.41%, B- grades of 2.94%, C grades of 0%, D grades of 1.47% and E grades of 4.41%. In addition, from this study, there was also an increase in students on affective, psychomotor and cognitive aspects. Affective aspects include discipline in task collection, honesty in conducting group assessments and honesty during tests, psychomotor aspects which include skills in applying basic principles and decision-making techniques From the results of descriptive analysis, it can be concluded that learning using cooperative and collaborative learning methods is proven to be able to increase student understanding of strategic decision-making techniques courses.